Is India prepared for an impending epidemic of cancers? - Pandve, Harshal T.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Cancer can have profound social and economic consequences for people in India, often leading to family impoverishment and societal inequity. Roughly one million new cases of cancer are added every year in India, which is one-fourth of that recorded in Europe. Recently published India’s National Health Profile 2013, projected that by 2020 India will see a 21% rise on an average in the incidence of cancer with a 19% increase in cancer among men, and a 23 % increase among women. Data from 25 population-based registries across the country was analysed and extrapolated to reach the projections. The incidence of mouth cancers will rise by 51%, 48% increase in the incidence of prostate cancers, 31% for liver cancers and 22% for lung cancers. Cancers of the brain, hypopharynx and oesophagus will dip very marginally. Gall bladder cancers will increase 45%, and ovarian cancers 28%. All cancers are projected to rise in women, including cervical and breast cancers, which will continue to be the two most common types.